CD11b‐deficient mice exhibit an increased severity in the late phase of antibody transfer‐induced experimental epidermolysis bullosa acquisita. Issue 12 (27th December 2017) - Deng, Fengyuan; Chen, Yan; Zheng, Junfeng; Huang, Qiaoniang; Cao, Xuetao; Zillikens, Detlef; Petersen, Frank; Yu, Xinhua
Abstract: CD11b, the α‐chain of β2 integrin Mac‐1, is involved in many activation processes of phagocytes. Depending on the respective autoimmune disorder, CD11b has been shown to exert pro‐inflammatory functions or be dispensable in their pathogenesis. Here, we investigated the role of CD11b in the pathogenesis of experimental epidermolysis bullosa acquisita (EBA), an autoimmune skin blistering disease mediated by autoantibodies to type VII collagen. Unexpectedly, in an antibody transfer‐induced model of EBA, CD11b‐deficient mice developed more severe disease symptoms than wild‐type mice in the late phase of the disease. Furthermore, as compared to wild‐type controls, CD11b‐deficient mice expressed increased levels of circulating IFN‐γ and IL‐4. Taken together, for the first time, our results suggest an anti‐inflammatory role for CD11b in experimental autoimmune diseases.